Desenvolvimento do conceito enfermagem em reabilitação para o contexto brasileiro - Dantas, Dandara Nayara Azevedo (2019)
Introduction: nursing in rehabilitation has not been widely established in Brazil. Many nurses are unaware of their role and importance as members of the rehabilitation team. It is believed that the existing conceptual gap of nursing in rehabilitation in this country may be contributing to this problem. Objective: to develop the concept Nursing in Rehabilitation for the Brazilian context, based on the hybrid model of concept development. Method: the Hybrid Concept Development Model was implemented in three components: Theoretical Phase, Field Phase and Final Analytical Phase. The Theoretical Phase was accomplished through the Scoping Review and analysis of 120 studies that describe the practice of nurses with a focus on rehabilitation. A Field Phase was conducted at the Onofre Lopes University Hospital and at the Specialized Center for Rehabilitation, both in Natal / RN, Brazil, through participations and interviews with nurses, members of the health team, patients and companions. Field Phase data was analyzed using content analysis. In the Analytical Phase, the results of the Theoretical and Field phases were compared, analyzed and integrated in the light of the Theoretical Model of Nursing for Life Activities, or to obtain a conceptual and operational definition for Rehabilitation Nursing, as well as the construction of a representative model of the concept, and a nursing instrument to assess life activities with a focus on rehabilitation. The research project was approved by the Ethics and Research Committee with CAAE 03986518.0.0000.5537. Results: theoretical data showed that the origin of the concept of nursing in rehabilitation in Brazil dates from the 1970s. In this phase, the concept was preceded by four antecedents, characterized by six attributes and nine consequent ones. In the field phase, five antecedents, five attributes and six consequences emerged. Nurses and nursing technicians reported little training and capacity to work in the context of rehabilitation. Health professionals described as nursing functions in rehabilitation: screening actions, assessment and monitoring of patients and family, guidelines for disease prevention, wound care, medication administration and body hygiene. In the analytical phase, all the antecedents, attributes and consequences assessed in the Theoretical Phase and Field Phase were judged appropriate. Therefore, all were considered for the development of the concept under study. Conclusion: the concept of rehabilitation nursing in Brazil is a practice developed by the nursing team in several services that make up the SUS, characterized by the identification of the patient's health conditions and the dependencies for carrying out activities and life; teaching and health education to the patient and / or family about the disease, treatment and self-care; compensatory care; management of human and material resources involved in the rehabilitation process; and emotional support.